FLAVANONES FROM THE WOOD OF Morus nigra WITH CYTOTOXIC ACTIVITY - Ferlinahayati Ferlinahayati; Yana Maolana Syah; Lia Dewi Juliawaty; Euis Holisotan Hakim (Indonesian Journal of Chemistry, 2013)
Two flavanone derivatives, norartocarpanone (1) and euchrenone a7 (2) had been isolated for the first time from the methanol extract of the wood of Morus nigra. The structures of these compounds were determined base on spectral evidence, including UV, IR, and NMR. The first compound also confirmed by comparison with the reported data. Cytotoxic properties of these compounds were evaluated against murine leukemia P-388 cells. Euchrenone a7 (2) was found more cytotoxic than norartocarpanone (1) with their IC50 7.8 and 12.7 mg/mL respectively.